Talen van geweld Stilte, informatie en misleiding in de Indonesische onafhankelijkheidsoorlog, 1945-1949 - Raben, Remco (Onafhankelijkheid, Dekolonisatie, Geweld en Oorlog in Indonesië 1945-1950, 2023)
While the Netherlands is still struggling with the question of how serious and widespread the violence was in the Indonesian War of Independence, that history can be found everywhere in Indonesia. Monuments and burial grounds are the silent witnesses of the battle and the stories of the war are still circulating. Remco Raben and Peter Romijn argue in this book that the way the Netherlands has long viewed the war in Indonesia has its origins in the language and the manipulation of information during that war. They investigate the mentality of administration and politics in Indonesia and the Netherlands and trace the path that knowledge about violence has taken, from the villages and fields in Indonesia to the desks of administrators, politicians and journalists in the Netherlands. This book shows how the cover-up of violence in Indonesia worked. It explains why war crimes and other large-scale violence against the Indonesian population were tolerated, how the army was able to dominate the provision of information about the war, how administrative mechanisms and mentalities promoted the concealment, how Dutch politicians looked away, and how Indonesian voices were systematically were ignored.